Theoretical and practical aspects of public-private partnerships - Smagulova, G. S. (Journal of Economic Research & Business Administration, 2016)
In recent years, the theme of public-private partnerships in various areas is becoming more and more relevant in the world. There is a tendency to strengthen cooperation between business and government. This is especially evident in areas such as power generation, transport, health and education. Of particular relevance the topic of public-private partnership has acquired in the context of the global financial crisis, due to which many sectors of Kazakhstan’s economy felt the need for government support. Therefore in this article the main features of public-private partnership, studied the organizational model of public-private partnership in Kazakhstan, characterized by certain types of public-private partnerships, as well as the main problems of public-private partnerships and suggested measures required for the successful the use of public-private partnership in Kazakhstan. The article also highlights the key challenges of public-private partnerships and the main benefits obtained from each side of the partnership as well as defined socially important areas in which the implementation of projects of public-private partnership is the most popular.